Index of Cultural Significance as a Potential Tool for Conservation of Plants Diversity by Communities in The Kerinci Seblat National Park - Asvic Helida; Ervizal Amir Muhammad Zuhud; Hardjanto Hardjanto; Yohanes Purwanto; Agus Hikmat (Jurnal Manajemen Hutan Tropika, 2015)
Kerinci community is one of the Indonesian indigenous people who live in Kerinci regency, Jambi Province. They have the local knowledge of the surrounding vegetation that has become a cultural unity with community. This study were aimed at analyzed the significance of culture plants and reviewing efforts to conserve plants based on cultural values in relation to Kerinci cultural. The study was conducted  at three locations  purposively,  they are Lempur Baru Village, Lama Tamiai Village and Ulu Jernih Village for eight months from October 2013 to May 2014. Data   was obtained by participatory observation approach, depth interview while the assessment of plant deployment society approach by point of view. The research data consist of data botany, plant utilization   and   assessment  plant deployment  while data analysis  using the formula Index of Cultural  Significance  (ICS)  adopted  from Turner.  The study shows  that the rice (Oryza sativa L) and cinnamon (Cinnamomun  burmanii Ness Ex.BI)) is a plant species that have important cultural value of 59 and 57 while  inggu  species  (Ruta  angustifolia (L). Pers) and onion  timber (Allium fistudosum Linn) has the lowest ICS, respectively 3. The Stimulus Tri Amar-Conservation analysis result that index of cultural significance (ICS) and kind of conservation by community has a range relationship.